PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE WARD AND PEPPARD (STUDI KASUS KAFE TEPI KOTA) - Tengku Michael Jimi Lanteng Lanteng; Christ Rudianto (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
Kafe Tepi Kota is a coffee shop that provides various variants of brewed coffee products. Kafe Tepi Kota is using Information Systems/Information Technology (IS/IT) to assist running business processes. The implementation of IS/IT at Kafe Tepi Kota still has various problems. It can be said that one of the causes is due to the use of IS/IT which is not based on IS/IT strategic planning. This research was conducted using a qualitative descriptive method and using the Ward and Peppard framework analysis method. It can be concluded by analyzing external/internal business conditions and external/internal IS/IT to produce IS/IT portfolio proposals needed to make Kafe Tepi Kota business processes more effective and efficient.